Meta-analysis of immunologic response after COVID-19 mRNA vaccination in solid organ transplant recipients. Issue 5 (May 2022) - Tang, Kefu; Wu, Xi; Luo, Ying; Wei, Zhiying; Feng, Liyun; Wu, Lei
Highlights: Impaired humoral and cellular immunity after COVID-19 vaccination in SOTRs was found. The seropositivity rate increased with the doses of mRNA vaccination in SOTRs. The seropositivity varies across different type of organ transplant recipients. Antimetabolite and belatacept therapy was associated with IgG seronegativity. COVID-19 mRNA vaccines are safe and well-tolerated in SOTRs.